Réponses

2013-01-17T15:13:18+01:00

A= (7x1/3 - 3 )²- (7x1/3 - 3) x (2x1/3+5)

 

A= (7/3 - 3)² - (7/3 - 3) x (2/3 + 5)

 

A= (7/3 - 3/1)² - ( 7/3 - 3/1) x (2/3 + 5/1)

 

voila a toi de finir si tu arrive pas envoie moi un message

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

+

2013-01-17T15:25:02+01:00

A = (49x²-42x+9)-(14x²+35x-6x-15)

    = 49x²-42x+9+14x²-35x+6x+15

     = 63x²-71x+24

 

Factorisation

(7x-3)(7x-3)-(2x+5)

= (7x-3)(7x-3+2x-5)

= (7x-3)(9x-8)

Pour x = 1/3

 

= (7/3-3)(9/3-8)

= (7/3-9/3)(9/3-24/3)

= -2/3*-15/3

= 30/3 = 10